Mewujudkan Desa Timbang Jaya yang Berdaya: Peran Strategis Mahasiswa Manajemen Dakwah UINSU dalam Pengabdian Mahasiswa - Hafiz Fatur Rahman; Anisah Setiani; Yasir Riski; Cyntia Bela; Muthia Mahfudzha (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Community service is one of the implementations of the Tri Dharma of Higher Education aimed at providing tangible contributions to community development. This study aims to describe the strategic role of students from the Department of Da'wah Management at Universitas Islam Negeri Sumatera Utara (UINSU) in the Student Community Service Program (PEMA) in Timbang Jaya Village and to analyze the implementation of community empowerment programs carried out during the activity. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that Da'wah Management students played strategic roles as facilitators, educators, motivators, and mediators in implementing community empowerment programs in the fields of religious development, education, institutional strengthening, and youth empowerment. The programs were implemented using a participatory approach that positioned the community as the primary actor in the development process, resulting in increased community participation, improved human resource capacity, and stronger collaboration among the community, village government, and the university. Despite several challenges, including limited implementation time and supporting facilities, the Student Community Service Program (PEMA) contributed significantly to creating a more independent, religious, and empowered Timbang Jaya Village.